Analisis Penentuan Komoditas dan Strategi Penumbuhan Kawasan Pengembangan Pengolahan dan Pemasaran Hasil Pertanian (KP3HP) di Kabupaten Bandung Barat - Warcito, Warcito; Jauhari, Asna (Jurnal Manajemen, 2015)
The purpose of this study was (1) Identify the leading commodity that will be developed in the area of program development processing and marketing of agricultural products (KP3HP), (2) analyzing alternative selection of superior commodities based on the results of the discussion using Bayes analysis method, and (3) to analyze the situation of growth KP3HP which encompasses groups of milk processing business in West Bandung regency. Data collection was performed by the method of desk study, observation and interview experts. Data processing is done by the method of AHP and SWOT analysis. Based on the results obtained identification of superior commodities in general for some commodities have been proposed as an alternative candidate for the commodities that will be applied in the implementation of the program KP3HP in 2013, namely: Rice (Foodstuffs), Potatoes (Foodstuffs), chilli (Hortikultra / Vegetables), Tomato (Horticulture / Vegetable), Paprika (Horticulture / Vegetable), Banana (Horticulture / Fruits), Coffee (Plantation), Tea (Plantation) and Milk (Livestock). Selected Commodities KP3HP of AHP structure developed dairy commodities ranks first with global weights 0.4976, followed by 0.1925 tea, chili 0.1712, and 0.1387 coffee. Based on the SWOT analysis, strategy can be developed including: (1) expanding and maintaining existing markets, (2) the promotion, (3) maintain and preserve the quality of products produced and (4) improve the distribution channel.